Pengaruh Pengawasan Dan Kepuasan Kerja Terhadap Kinerja Pegawai Melalui Organization Citizenship Behavior pada Kantor Wilayah Kementerian Agama Provinsi Sumatera Utara - Indra Sakti Nasution; Hazmanan Khair (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Employee performance is a determining factor for the company's success. The problem that occurs in this study is a decrease in performance by employees at the Regional Office of the Ministry of Agma, North Sumatra Province. The decline in performance is seen from the lack of supervision and attention made by superiors to their subordinates; There are employees who are still working on individual jobs; and demands of work roles that exceed the capabilities of employees. This study aims to determine the effect of supervision and job satisfaction on performance either directly or indirectly through Organizational Citizenship Behavior (OCB). The number of samples in this study were 66 employees. Data collection methods are interviews and questionnaires. Methods of data analysis using regression and path analysis. The results showed that supervision and job satisfaction had a direct or indirect effect on employee performance through OCB in a positive direction. OCB is proven to be able to mediate the effect of supervision on employee performance, but OCB is not able to mediate the effect of job satisfaction on employee performance in the Ministry of Agma Region of North Sumatra Province.